PREDIKSI TABEL INPUT-OUPUT INDONESIA SECARA DINAMIS TAHUN 2000-2010 DENGAN MENGGUNAKAN MIOTRINA - HENDRANATA, ANTON (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 2 Juli 2007)
ABSTRACT The goal of this research is to predict Indonesia’s input-output table, especially on technology coefficient matrix from 2000 to 2010. The prediction used the econometrics model which is called MIOTRINA. MIOTRINA is the hybrid model which is combined the approach between the adjustment of Marshallian and Walrasian in achieving the equilibrium point. This model is a simultaneous equation which has dynamic characteristic and consists of 156 equations of the year 1980-2005. The equation of parameters is estimated by using the combination of three estimation methods are: (1) Ordinary Least Square, (2) First Order of Autoregressive, and (3) Second Order of Autoregressive. The model is then formulated by using Gauss-Seidel iteration method. The result of the study indicated that: (1) MIOTRINA is able to produce Indonesia’s input-output table which is dynamic by inputting the price factor, (2) the prediction result of input-output table is excellent due to the production input which is needed by each sector is logic and fit to the requirement of Leontief inverse matrix and technology coefficient matrix condition, and (3) the main intermediate input structure is relatively stable between the period 2005-2010 compared with the period 2000-2005. This condition is supported by the fact that the economy between the period 2005-2010 is conducive and relative stable. Keywords: Hybrid, Econometric Input-Output, Marshallian Adjustment, Walrasian Adjustment, Multiplier, Input Structure ABSTRAK Tujuan dari penelitian ini adalah memprediksi tabel input-output Indonesia, khususnya matriks koefisien teknologi tahun 2000-2010 dengan menggunakan pendekatan model ekonometrika yang disebut MIOTRINA. MIOTRINA merupakan model hibrida yang menggabungkan pendekatan penyesuaian output (Marshallian adjustment) dan penyesuaian harga (Walrasian adjustment) dalam mencapai titik keseimbangannya. Model ini merupakan persamaan simultan yang sifatnya dinamis, terdiri atas 156 persamaan tahun 1980-2005. Parameter persamaan diduga dengan menggunakan tiga kombinasi metode pendugaan yaitu: (1) Ordinary Least Square, (2) First Order of Autoregressive, dan (3) Second Order of Autoregressive. Kemudian, disolve secara bersama-sama menggunakan metode Gauss-Seidel iteration. Hasil penelitian menunjukkan bahwa: (1) MIOTRINA mampu menghasilkan tabel input-output Indonesia secara dinamis dengan memasukkan faktor harga, (2) hasil prediksi tabel input-output Indonesia sangat memuaskan karena input produksi yang diperlukan oleh setiap sektor masuk akal dan telah memenuhi persyaratan dari matriks kebalikan Leontief dan matriks koefisien teknologi, dan (3) struktur input antara utama relatif stabil selama periode 2005-2010 dibandingkan periode 2000-2005. Kondisi ini didukung oleh perekonomian yang kondusif dan stabil selama periode 2005-2010. Kata Kunci: Hibrid, Ekonometrik Input-Output, Penyesuain Marshallian, Penyesuaian Walrasia, Multiplier, Struktur Input
Keywords: Hybrid, Econometric Input-Output, Marshallian Adjustment, Walrasian Adjustment, Multiplier, Input Structure (Hibrid, Ekonometrik Input-Output, Penyesuain Marshallian, Penyesuaian Walrasia, Multiplier, Struktur Input)